Smart security door system using SMS based energy harvest - Abdullah Hamas; Amgad Muneer; Suliman Mohamed Fati (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Over the last decade, different studies have been conducted to increase security to identify sensor technology and provide alternative energy with other energy harvest techniques such as vibration energy harvester and sun energy harvester. There is no combinational approach to utilize the door to create energy and use it for security measures in the literature, making our system different and unique. This proposed system comprises the security and the energy harvest; the security section utilizes a motion detector sensor to detect intruders. For instance, the magnetic door lock type firmly locks the door, which can only open with a generated password. On the other side, the energy harvest section utilizes the door motion to generate electricity for the system, which solves power shortage and limited battery life issues. Moreover, this study includes a GSM module that allows authorized owners to receive a generated password as a security enhancement. This design mainly focuses on improving or optimizing the conventional security doors' overall performance as sliding door, panel door, or revolving door. The experimental results show the system efficiency in terms of power generation and the time needed to authenticate the property owner. Notably, the power generator can generate electricity more rapidly, while the needed time to receive the mobile device's security code is around 3.6 seconds.